1994
DOI: 10.1007/bf01400660
|View full text |Cite
|
Sign up to set email alerts
|

Craniocerebral epidermoid and dermoid tumours: a review of 32 cases

Abstract: We reviewed 22 epidermoid and 10 dermoid tumours of the skull and brain from patients operated on consecutively at Henry Ford Hospital between 1975 and 1991. There were 19 intradural (16 epidermoid, 3 dermoid) and 13 extradural (6 epidermoid, 7 dermoid) lesions. The average age at presentation was 35 years for patients with epidermoids and 15 years for those with dermoids. Common clinical presentations for patients with intradural lesions included headache, visual deficits, and seizures, whereas patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0
17

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 36 publications
2
80
0
17
Order By: Relevance
“…21,22 They are most commonly encountered in the posterior fossa cisterns, parasellar cisterns, and fourth ventricle. 10 Their occurrence inside the brain parenchyma is not commonly encountered. 8,9,24,29 In a recent review of all intraaxial dermoid cysts, the authors found only 4 cases of frontal dermoid cysts, emphasizing the novelty of our case.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 They are most commonly encountered in the posterior fossa cisterns, parasellar cisterns, and fourth ventricle. 10 Their occurrence inside the brain parenchyma is not commonly encountered. 8,9,24,29 In a recent review of all intraaxial dermoid cysts, the authors found only 4 cases of frontal dermoid cysts, emphasizing the novelty of our case.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, epidermoid cysts arise in the cranial diploe of the middle ear region or frontal bone, where they present as a lytic defect. Unlike dermoid cysts, epidermoid cysts often occur laterally, without a preference for midline sites (1,4,8,10,13) .…”
Section: Discussionmentioning
confidence: 99%
“…The lining epithelium of epidermoid cyst is immunoreactive for cytokeratins and epithelial membrane antigen (EMA). In contrast to cysts of neuroglial origin there is no immunoreactivity of the lining epithelium with antibodies to glial fibrillary acidic protein (GFAP) (2,4,6,8,13,14) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidermoid cyst is frequently associated with developmental abnormalities such as spina bifida, dermal sinus, meningomyelocele, diastematomyelia and enterogenous cysts or one or more of the mesodermal malformations, particularly those involving the vertebrae (e.g., hemivertebrae, absent vertebrae, fused vertebrae, butterfly vertebrae, midline bony spurs). 6,11,18 Acquired epidermoid cysts have been found years after single or multiple lumbar spinal punctures or meningomyelocele repairs and are thought to result from iatrogenic penetration of skin fragments. 12 The epidermoid cyst is lined by simple stratified squamous epithelium resting on an outer layer of connective tissue.…”
mentioning
confidence: 99%